Orchid mycorrhizal fungal diversity of Orchis militaris habitats - Ouanphanivanh, Noémi; Illyés, Zoltán; Rudnóy, Szabolcs; Bratek, Zoltán (JOURNAL OF LANDSCAPE ECOLOGY, 2007)
We have investigated the symbionts of Orchis militaris and the fungal communities at some of the habitats of Orchis militaris. Symbiotic fungi were identified from orchid roots and from in situ germinated protocorms by molecular methods, based on the sequence of nrITS region. Four genus-like taxa of orchid mycorrhizal fungi could be identified from Orchis militaris: Epulorhiza I, Epulorhiza II, Ceratobasidium and Sebacina. This high fungal diversity can be in connection with Orchis militaris ability to live at diverse habitats.Assaying the fungi at some of the Orchis militaris habitats, the highest symbiotic fungal diversity was found at wetlands while dry and/or disturbed habitats showed the poorest diversity, only or mainly with Epulorhiza II symbionts.Comparing the symbionts of adult Orchis militaris plants and protocorms, we discovered, that the protocorms were infected only with Epulorhiza II fungi, while adult plants lived in symbiosis with more genera of orchid mycorrhizal fungi.
Keywords: orchid mycorrhiza; specificity; Epulorhiza; protocorm